(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Chetan Bhagat tries to portrait the old traditions of the society. He speaks about the mindsets of the people, discriminations between woman and man. Woman’s having their own goals in their life. His writing holds no restraints and so are the characters of the novels. The main objective of his writing is to appreciate the liberty, rights, and views of women.